Evaluation of the Pharmacokinetics of Felcisetrag (TAK‐954), a 5‐HT4 Receptor Agonist, in the Presence and Absence of Itraconazole, a Potent CYP3A4 Inhibitor. Issue 2 (6th January 2022) - Chen, Chunlin; Zhang, Liming; Almansa, Cristina; Rosario, Maria; Cwik, Michael; Balani, Suresh K.; Lock, Ruth
Abstract: The 5‐hydroxytryptamine type‐4 receptor agonist felcisetrag (TAK‐954) is being investigated for improving gastrointestinal motility in postoperative gastrointestinal dysfunction. Polypharmacy often occurs in this setting, and as in vitro data indicate, felcisetrag is primarily metabolized by cytochrome P450 (CYP) 3A4, its CYP3A4‐mediated drug‐drug interaction potential requires consideration. This phase 1, fixed‐sequence, open‐label, crossover trial (ClinicalTrials.gov identifier NCT03173170) investigated the effect of itraconazole, a potent CYP3A4 inhibitor, on felcisetrag pharmacokinetics in healthy adults. Over 2 study periods (period 1, 6 days; period 2, 9 days), participants received a single felcisetrag 0.2‐mg intravenous dose (day 1, period 1; and day 4, period 2), and once‐daily oral itraconazole 200‐mg doses (days 1‐8, period 2). For felcisetrag alone, felcisetrag total systemic exposure was lower than with itraconazole coadministration. The geometric mean ratio for area under the plasma concentration–time curve from time 0 to infinity of felcisetrag plus itraconazole: felcisetrag alone was 1.49 (90% confidence interval, 1.39‐1.60). Peak exposure was similar between regimens (geometric mean ratio, 1.06; 90% confidence interval, 0.96‐1.18), and both treatments were well tolerated. These data suggest limited CYP3A4‐mediated drug‐drug interaction inhibition for felcisetrag.